Assessment of the Impact of Pile Characteristics on the Horizontal Displacement of Retaining Walls under Heavy Rainfall: A Case Study in Vietnam - Nguyen, Phuong Tuan; Vo, Luan Nhat; Dang, Truong Xuan; Tran, Hoa Van Vu; Nguyen, Tuan Anh (Engineering, Technology & Applied Science Research, 2025)
This study evaluates how pile characteristics influence the Horizontal Displacement (Ux) of river retaining walls in Ho Chi Minh City, Vietnam, during heavy rainfall, which floods the walls, while the river water level remains at its lowest. The study utilizes Finite Element Method (FEM) in combination with statistical methods, such as linear regression and Pearson correlation, to examine the effects of pile factors. These factors are the Number of Piles (NoP), Pile Spacing (PS), Pile Diameter (PD), and Pile Type (PT) based on the Ux of the river retaining walls. Finite element simulations are conducted across different scenarios to evaluate the impact of the aforementioned factors under dynamic environmental conditions. The study results show significant variation in the Ux of the retaining walls based on each factor. PS and PD have a strong influence on Ux, with correlation coefficients of 0.585 and -0.549, respectively. This indicates that a larger PS increases displacement, while a smaller PD also leads to greater displacement. In contrast, NoP has a weak correlation with Ux. The linear regression models suggest that these factors do not have an equal impact on the retaining wall stability. It is concluded that optimizing the pile characteristics, particularly PS and PD, can help minimize Ux. This enhances the stability of river retaining walls under harsh climatic conditions.